An integrated maritime surveillance system based on high-frequencysurface-wave radars, part 2 operational status and system performanc. - Ponsford, Anthony M.; Sevgi, Levent; Chan, Hing C.
For pt.1 see ibid., vol.43, no.4, p.28-43 (2001). An integrated maritime surveillance (IMS) system, based on high-frequency surface wave radars (HFSWR), for monitoring surface and low-level air activity within the 200 nautical mile (nm) Exclusive Economic Zone (EEZ) is described in this two-part paper. The science behind the long-range performance of HFSWR was presented in Part 1(Sevgi et al. 2001). The system described was installed on Canada's east coast, where it is being used to demonstrate continuous, all-weather surveillance of the EEZ to beyond 200 nm. The system consists of two land-based HFSWRs and an operations control center (OCC). The two unmanned radars provide coverage of the Grand Banks region of Newfoundland, renowned for its offshore resources, particularly fish and oil. The system has been designed to assist authorities to more efficiently monitor such illegal activities as drug trafficking, smuggling, piracy, illicit fishing and illegal immigration. In addition, the system may be used for tracking icebergs, environmental protection, search and rescue, resource protection, sovereignty monitoring, and remote sensing of ocean surface currents and winds. Extensive performance testing of the system has been conducted using the two fully functional radars. It is shown that the HFSWR system complements existing surveillance assets to dramatically increase the effectiveness of air and surface reconnaissance missions by vectoring them directly to targets of interest.
Keywords: Marine radar; Radar applications; Radar interference; Radar target recognition; Radar cross sections; Search radar; HF radio propagation; Electromagnetic surface waves; Sea surface electromagnetic scattering; Phased array radar; Pulse Doppler radar